Stochastic and global optimization - Dzemyda, Gintautas; Šaltenis, Vydūnas; Zhilinskas, A. (Nonconvex optimization and its applications ;, 2002)
This title emphasizes the statistical approach to global and discrete optimization, though applications to optimal design and to mathematical finance are also presented. The results of various subjects are summarized and the prospects for developments are justified.